Pasolini renascentista - Soares, Luiz Felipe (2019)
This essay intends to relate the notion of Renaissance as presented by ABy Warburg to the one that the Italian director Pier Paolo Pasolini, as a reader of Chaucer, presents as on his cinematographic works.